L’« arte » del giardino nell’Europa di età moderna : ipotesi di lavoro e prospettive di ricerca - Chiara Santini (Projets de Paysage)
Based on new researches recently developed in the history of gardens, relating to the gardener's knowledge and savoir-faire at the Modern period, this article presents the first results of a research about the profession of gardener in France at the 17th century. The analysis is based on a corpus of twenty texts on horticulture and gardening published during the 17th and 18th centuries by gardeners, flowers collectors, agronomists and amateurs à i.e. authors who belong to a milieu less erudite than the milieu who elaborated the following Treaties : Boyceau de la Barauderie and de Dezallier d'Argenville. The article attempts to draw the reception and the participation of the representatives of the profession in the definition of the « art of garden» and the theories related to it.